Inhibition of Aflatoxin B1 Synthesis in Aspergillus flavus by Mate (Ilex paraguariensis), Rosemary (Rosmarinus officinalis) and Green Tea (Camellia sinensis) Extracts: Relation with Extract Antioxidant Capacity and Fungal Oxidative Stress Response Modulation - Anthony Al Khoury; André El Khoury; Ophélie Rocher; Pamela Hindieh; Olivier Puel; Richard G. Maroun; Ali Atoui; Jean-Denis Bailly (Molecules, 2022)
Plant extracts may represent an ecofriendly alternative to chemical fungicides to limit aflatoxin B1 (AFB1) contamination of foods and feeds. Mate (Ilex paraguariensis), rosemary (Romarinus officinalis) and green tea (Camellia sinensis) are well known for their beneficial properties, which are mainly related to their richness in bioactive phenolic compounds. AFB1 production is inhibited, with varying efficiency, by acetone/water extracts from these three plants. At 0.45 µg dry matter (DM)/mL of culture medium, mate and green tea extracts were able to completely inhibit AFB1 production in Aspergillus flavus, and rosemary extract completely blocked AFB1 biosynthesis at 3.6 µg DM/mL of culture medium. The anti-AFB1 capacity of the extracts correlated strongly with their phenolic content, but, surprisingly, no such correlation was evident with their antioxidative ability, which is consistent with the ineffectiveness of these extracts against fungal catalase activity. Anti-AFB1 activity correlated more strongly with the radical scavenging capacity of the extracts. This is consistent with the modulation of SOD induced by mate and green tea in Aspergillus flavus. Finally, rutin, a phenolic compound present in the three plants tested in this work, was shown to inhibit AFB1 synthesis and may be responsible for the anti-mycotoxin effect reported herein.